(untitled) (International Journal of Economics Management and Social Science, 2026)
Background: Urban marginal communities represent concentrated sites of social deviance, shaped by poverty, exclusion, and the erosion of formal institutional authority. Informal social control mechanisms—including community norms, peer pressure, family supervision, and neighborhood surveillance—play a critical yet understudied role in regulating deviant behavior within these settings. Objective: This study aims to analyze the phenomena of social deviance in urban marginal communities and evaluate the effectiveness of informal social control mechanisms in moderating such behavior through a sociological lens. Methods: A systematic literature review was conducted using peer-reviewed sources published between 2019 and 2025, drawn from Scopus, Web of Science, and Google Scholar, using keywords including social deviance, informal social control, urban marginality, community norms, and labeling theory. Results: Findings indicate that social deviance in marginal urban communities is produced by a convergence of structural factors—including poverty, unemployment, housing insecurity, and social disorganization—and symbolic factors such as stigma, identity disruption, and weakened normative consensus. Informal social control mechanisms retain significant regulatory capacity, particularly when grounded in strong community cohesion, reciprocal social trust, and culturally resonant norms. However, their effectiveness is constrained by urbanization, social fragmentation, and the criminalization of poverty through formal control systems. Conclusion: Informal social control remains a vital complement to formal law enforcement in urban marginal settings, and its effectiveness is maximized when community-based institutions are supported rather than supplanted by state intervention. Keywords: social deviance, informal social control, urban marginality, labeling theory, social disorganization, community cohesion